MiR‐141‐3p regulates saturated fatty acid‐induced cardiomyocyte apoptosis through Notch1/PTEN/AKT pathway via targeting PSEN1. Issue 4 (12th December 2021) - Xin, Xin; Duan, Lian; Yang, Huimin; Yu, Hang; Bao, Yandong; Jia, Dalin; Wu, Nan; Qiao, Ying
Abstract: It has been reported that miR‐141‐3p levels are markedly upregulated in the cardiomyocytes of obese rats induced by a high‐fat diet. However, the role of miR‐141‐3p in myocardial lipotoxicity remains elusive. In the present study, the role of miR‐141‐3p in lipotoxic injury of H9c2 cells induced by palmitic acid (PA) and its possible mechanisms were assessed. The results indicated that miR‐141‐3p was significantly upregulated in PA‐induced cardiomyocytes. miR‐141‐3p inhibitor enhanced the cell viability, reduced the release of lactate dehydrogenase (LDH), creatine kinase‐MB (CK‐MB), and troponin I (CTN‐I), decreased cell apoptosis rate, and repressed the activation of mitochondrial apoptosis pathway in PA‐treated H9c2, whereas treatment with miR‐141‐3p mimics resulted in the opposite effects. Mechanistically, it was further revealed that miR‐141‐3p could specifically bind to presenilin 1 (PSEN1) 3′UTR, and upregulating miR‐141‐3p levels reduced the expression of PSEN1, thereby inhibiting the activation of the Notch1/PTEN/AKT pathway. Additionally, inhibition of Notch1/AKT signaling pathway by its inhibitor could abrogate the effect of miR‐141‐3p on mitochondrial‐mediated apoptosis induced by PA. In conclusion, the present study demonstrates that miR‐141‐3p regulates saturated fatty acid‐induced cardiomyocyte apoptosis through Notch1/PTEN/AKT pathway via targeting PSEN1, which gains a new insight into the mechanisms of myocardial lipotoxic injury.